Development of an Improvised PIM-Integration Design Prototype for Organizational Efficiency - S.Babu2, Prof.Dr.G.Manoj Someswar1 (International Journal of Scientific Research and Management (IJSRM), 2013)
Personal Information Management (PIM) describes the acquisition, organization, andretrieval of information by an individual computer user. Studies have shown that many users struggle tomanage the volume and diversity of information that they accumulate. Much design activity has beenaimed at improving integration between different PIM tools, such as file and email managers. However,in terms of making a systematic contribution to HCI knowledge, much of this cross-tool design can becriticized for a lack of empirical grounding and evaluation.The research described in this thesis employs a user-centered design methodology to deepenunderstanding of PIM, and in particular to provide guidance for PIM-integration design. The research isgrounded in an exploratory study of file, email and bookmark management, which is differentiated fromprevious studies by its cross-tool nature. The study offers several contributions including observationsof participants’ multiple organizing strategies – in both tool-specific and cross-tool contexts. Also,many participants had significant numbers of over-lapping folders that appeared in multiple toolcontexts. This finding informs the design of Workspace Mirror, a novel PIM-integration prototype,which allows a user to mirror changes between their file, email and bookmark folders.The final stage of the research is a dual-purpose field study, aimed evaluating Workspace Mirror, and investigating PIM behaviour over time. Participant feedback indicates that mirroring is more appropriatefor top-level folders, and illuminates a trade-off between organizational consistency and organizational flexibility. The study also reveals the incremental nature of changes in organizing strategy, and highlights the supporting nature of PIM. These and other empirical findings are used to improve previous descriptive models of PIM behaviour. Furthermore, a number of design and methodologicalguidelines are developed. In particular, the authors emphasize the importance of assessing the strengths and weaknesses of PIM designs from both tool-specific and cross-tool perspectives.